Incidence of rhizome rot of ginger in some selected areas of Bangladesh and the causal pathogens associated with the disease (Bangladesh Journal of Agricultural Research, 2019)
Ginger (ZingiberofficinaleL.) belongs to family Zingiberaceae is an important oriental spice crop. Ginger is high value crop which grows well in warm and humid climate and is cultivated from sea level to an altitude of 1500 meters above sea level (Kandinnan, et al. 1996). It has special significance for tropical countries where it is produced and consumed in large quantities (Islam, 2017; BARI, 2012, 2013 and 2014). The aromatic rhizomes are used as spice and medicine. Major producers of ginger in the world are India, Jamaica, Sierra Leone, Nigeria, China, Japan, Taiwan and Australia (Rana and Sharma, 1998). Ginger is much more used in Bangladesh as a spice and is cultivated more or less all over the country. In the country produced only 74380 metric tons of ginger from 9120 ha of land and the yield per hectare was 8.15 kg (BBS, 2011). But average yield is low as compared to other ginger growing countries of the world. The production is not enough to fulfill the annual requirement of the country. So every year a good amount of ginger is imported in exchange of foreign currency. Like many countries diseases are the major limiting factors for ginger cultivation in Bangladesh. Among the diseases, rhizome rot is the most devastating one caused by Pythium aphanidermatum, Fusariumoxysporum, Sclerotiumrolfsiiand Ralstoniasolanacearumthroughout the world (Chauhan and Patel, 1990; Dohrooet al. 1987 and Iyer, 1987). The pathogens involved decide the nature of the damage and symptom expression .The major pathogens involved with rhizome rot are viz., species of Pythium causing soft rot, Fusariumspp. causing yellows or wilt and Ralstoniasolanacearumcausing bacterial wilt (Elliot, 2003). Basal rot caused by Sclerotiumrolfsiiwhich appears later in the season in some cases. All these pathogens are known to form complexes with nematodes leading to synergistic effect on the severity of the disease. They predispose the crops to secondary pathogens (Sarma, 1994).Loss due to rhizome rot is estimated in many countries and the main pathogens associated with rhizome rot are the fungi such as Pythium spp. and Fusariumspp, bacteria like Ralstoniasolanacearumand nematode (Elliot, 2003). It may cause losses to the extent of 50% or more due to soft rot ((Islam, 2017; BARI, 2012, 2013 and 2014; Joshi and Sharma, 1982) and sometimes total failure of the crops in the tropical regions of India (Fageriaet al, 2006); 70% rhizomeproduction is reduced due to the infection caused by Pythium spp. and Fusariumspp. in Nepal (Anon., 2012) and 5-30% losses occurred in Fiji and Australia by Pythium myriotylum(Stirlinget al., 2009). Soil, water and infected planting materials are the main source of perpetuation of these pathogens (Dohroo, 2005). Pythium spp. is able to persist in soil over decay by means of encysted zoospores, oospores and sporangia. Pythium spp also can survive in air dry muck soil for up to 12 years (Hoppe, 1966). Pythium spread via infested rhizomes (Trujillo, 1964) and as oospores surviving in debris in the soil (Dohroo, 2005). Infection started from contaminated planting materials, saprophytically living fungus in the soil or on trash of previous ginger crops. The soft rot pathogen generally have quite a wide host range and can survive on other host plants so this makes it difficult to control in the field. In the past Pythium aphanidermatumwas known as the sole causal agent of rhizome rot of ginger and was successfully controlled by the technology developed by Plant Pathology Division, BARI. But during the last few years that technology was not working well and it was noticed that some other fungal and bacterial association were involved with such rot. As the crop is cash crop so it is prime need to identify the causal agents of rhizome rot through intensive survey which will help to modify the existing technology for managing the disease in future. The present research work was undertaken to determine the incidence of rhizome rot of ginger and its causal agents.Bangladesh J. Agril. Res. 44(3): 569-576, September 2019